Overview of Water Quality in Maintening Tilapia Fish (Oreochromis niloticus) in Floating Net Cages in Lihung Village, Karang Intan, Banjar District, South Kalimantan - Rina Iskandar; Yulius Kisworo; Andika Cipta Maulana (Jurnal Penelitian Pendidikan IPA, 2024)
Water quality is the quality characteristics required for certain uses of various water sources. The research aims to analyze water quality conditions, water physics (temperature, water color, depth, brightness, and current), water chemistry (pH, BOD, DO, ammonia, and phosphate), and water biology (plankton) in river flows in the village Lihung, diamond coral. This research was conducted in the river waters of Lihung Village, Karang Intan District, Banjar Regency, South Kalimantan Province. Determination of sampling points was carried out using purposive sampling. Physical and chemical parameters in the Lihung Village River that support the development of aquaculture are, temperature, pH, water color, dissolved oxygen (DO), nitrate, while parameters that do not support the development of aquaculture are, brightness, depth, current, biochemical oxygen demand (BOD), ammonia. Physical and chemical parameters still support the survival of fish, although they are still supportive, there are several parameters whose values exceed the water quality standards that have been set. Judging from the pollution index value, the Lihung River is a lightly polluted body of water. So overall the Lihung River is still good for developing fisheries cultivation. The biological parameters of plankton in the Lihung River are 3 genus variants, namely, Bacillariophyceae, Chlorophyceae, and Copepada, with the dominant plankton in the waters being the genus Bacillariophyceae, which is a class of plankton that is good for aquaculture in rivers, with a brownish green river color. Cluster 1 contains stations II and III which are similar in all water quality parameters (temperature, water color, depth, brightness, water flow, pH, DO, ammonia, BOD, phosphate and plankton). From the results of these observations, good water quality results were obtained at both stations. This cluster 2 contains station I which has significant differences in water quality from stations II and III, station I has BOD, ammonia, brightness, depth, and currents that do not support fish cultivation.